Magnetic Field Enhancement of Water Evaporation in Confined Spaces - Venkatesan, Munuswamy; Coey, John (My University, 2023)
Water is studied in confined environments where it evaporates into its own vapor. Simultaneous experiments are conducted for 0.4–0.5 µL droplets confined at the center of 54 mm long microchannels with a cross section of 0.38 mm 2 in the presence and absence of a 300 mT magnetic field. Results are compared with those for water in half-filled 100 mL beakers. The magnetic enhancement of the evaporation rate is much greater in the microchannels, where effects range up to 140% even though the air is saturated with water vapor, as compared to 12 ± 7% in a 500 mT field in the beakers. The average steady state, no-field evaporation rate of 0.13 kg ⋅ m −2 ⋅ h −1 in the microchannels is roughly double that in the beakers, but less than the value expected at an open surface in still air. The magnetic enhancement is analyzed in terms of the ortho and para nuclear isomers of water vapor, which behave as independent gasses. The ortho:para ratio in fresh vapor is close to 2:3, and quite different from the 3:1 equilibrium ratio in ambient air. Evaporation is increased by the gradient of the applied magnetic field, which dephases the Larmor precession of the two proton spins of hydrogen in a water molecule and tends to equalize the isomeric populations in the vapor, thereby increasing the evaporation rate.
PUBLISHED
Keywords: Microfluidic channels; Magnetochemistry; Evaporation of water in magnetic field; Ortho and para water vapor; Nanoscience & Materials; Applied physics; Condensed matter, electronic, magnetic and superconductive properties; Magnetism and spin electronics; Nanotechnology; Education